SIRT1: A Potential Therapeutic Target in Autoimmune Diseases - Shen, Pan; Deng, Xuan; Chen, Zhe; Ba, Xin; Qin, Kai; Huang, Ying; Huang, Yao; Li, Tingting; Yan, Jiahui; Tu, Shenghao (Frontiers in Immunology, 2021)
The morbidity and mortality of autoimmune diseases (Ads) have been increasing worldwide, and the identification of novel therapeutic strategies for prevention and treatment is urgently needed. Sirtuin 1 (SIRT1), a member of the class III family of nicotinamide adenine dinucleotide (NAD+)-dependent histone deacetylases, has been reported to participate in the progression of several diseases. SIRT1 also regulates inflammation, oxidative stress, mitochondrial function, immune responses, cellular differentiation, proliferation and metabolism, and its altered functions are likely involved in Ads. Several inhibitors and activators have been shown to affect the development of Ads. SIRT1 may represent a novel therapeutic target in these diseases, and small molecules or natural products that modulate the functions of SIRT1 are potential therapeutic agents. In the present review, we summarize current studies of the biological functions of SIRT1 and its role in the pathogenesis and treatment of Ads.